A Review of How Building Mitigates the Urban Heat Island in Indonesia and Tropical Cities - Dany Perwita Sari (Earth, 2021)
A consequence of urbanization was the intensification of urban heat islands, especially in tropical cities. There have been rapid developments in infrastructure that have displaced open spaces. Meanwhile, Indonesia has a tropical climate directly affected by climate change. A high priority has been placed on adaptation measures to address issues such as sea-level rise, increased extreme weather, and threats to ecosystems and biodiversity. There is still a lack of specific knowledge regarding tropical climate in urban areas. In this paper, the author examines how building and urban planning affect urban heat islands in the tropics. According to the review, early planning and building based on local weather data can reduce the energy consumption and minimize the UHI effect. Furthermore, a media campaign and early education should increase awareness about adaptation measures between governments and citizens. Based on the findings from this study, some recommendations are offered for future urban planning, especially for tropical climates, to reduce UHI effects.